Characterization of complete chloroplast genome of Malus sylvestris L. Issue 2 (3rd July 2019) - Xu, Yunfang; Zhao, Yujie; Zhao, Xueqing; Chen, Xuesen; Yuan, Zhaohe
Abstract: The European wild apple ( Malus sylvestris L.) is an important economical fruit crop. In this present study, we characterized the complete chloroplast (cp) genome sequence of Malus sylvestris L. The complete cp genome is 159, 926 bp in length with a typical quadripartite structure, containing a large single-copy region (88, 064 bp), a small single-copy region (26, 353 bp) and a pair of inverted repeat regions (19, 157 bp each). A total of 110 unique genes were found in the newly sequenced genome, including 78 protein-coding genes, 28 tRNA genes, and 4 rRNA genes. Of these, 6 protein-coding genes, 7 tRNA genes, and all 4 rRNA genes are duplicated in the inverted regions. A phylogenetic tree was reconstructed using the neighbor-joining method based on the full length of cp genomes within genus Malus . The result showed that M. sylvestris L. was clustered together with the cultivated apple. The complete cp genome could provide valuable information for understanding the phylogenetic relationships within the genus Malus .